A Large-Scale Survey of the Bacterial Communities in Lakes of Western Mongolia with Varying Salinity Regimes - Kshitij Tandon; Bayanmunkh Baatar; Pei-Wen Chiang; Narangarvuu Dashdondog; Bolormaa Oyuntsetseg; Sen-Lin Tang (Microorganisms, 2020)
In recent years, climate change coupled with anthropogenic activities has led to monumental changes in saline lakes which are rapidly drying up across the globe and particularly in Central Asia. The landlocked country of Mongolia is rich in lakes which have remained primarily undisturbed by human impact, and many of these lakes have varying salinity regimes and are located across various geographical landscapes. In this study, we sampled 18 lakes with varying salinity regimes (hyperhaline, mesohaline, oligohaline, and polyhaline) covering 7000 km of western Mongolia and its various geographical landscapes (Gobi Desert, forests, and steppe). We identified that the bacterial communities that dominate these lakes are significantly influenced by salinity (p < 0.001) and geographical landscape (p < 0.001). Further, only five zOTUs were shared in all the lakes across the salinity regimes, providing evidence that both local and regional factors govern the community assembly and composition. Furthermore, the bacterial communities of hyperhaline lakes were significantly positively correlated with salinity (ANOVA, p < 0.001) and arsenic concentrations (ANOVA, p < 0.001), whereas bacterial communities of mesohaline and polyhaline lakes situated in forest and steppe landscapes were positively correlated with temperature (ANOVA, p < 0.001) and altitude (ANOVA, p < 0.001), respectively. Functional predictions based on the 16S rRNA gene indicated enrichment of KEGG Ontology terms related to transporters for osmoprotection and -regulation. Overall, our study provides a comprehensive view of the bacterial diversity and community composition present in these lakes, which might be lost in the future.